Akuntabilitas Pengelolaan Dana Zakat Pada Badan Amil Zakat Nasional Kabupaten Kolaka - Athiyah, Nikmatul; Idrus, Mukhammad; Anwar, Azwar (Indo-Fintech Intellectuals: Journal of Economics and Business, 2024)
This study aims to: To determine the accountability of zakat fund management in BAZNAS Kolaka Regency based on Law No. 23 of 2011 and PSAK 109. The variable in this study is a single variable. The population in this study is the management of BAZNAS Kolaka Regency and the report on the management of zakat funds. The sample of this study is the management of BAZNAS Kolaka Regency consisting of four people representing each collection division, distribution division, utilization division, and reporting division and report on zakat fund management in 2021. Data collection techniques are carried out by interviews and documentation. The data analysis uses qualitative descriptive, comparative analysis and the Gross Conformity Index formula. The results of this study show that the management of zakat in BAZNAS Kolaka Regency, includes the process of collecting, distributing, utilizing, and reporting zakat in accordance with Law No. 23 of 2011. In terms of recognition, measurement and presentation have been in accordance with PSAK 109 based on IKK calculations. However, in terms of disclosure, the implementation of PSAK 109 is not appropriate based on the calculation of the IKK. Thus, BAZNAS of Kolaka Regency is not fully compliant with PSAK 109